2005
DOI: 10.1038/sj.npp.1300824
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noncompetitive NMDA Receptor Blockade on Anterior Cingulate Cerebral Blood Flow in Volunteers with Schizophrenia

Abstract: Schizophrenia may be related to dysfunctional glutamatergic activity, specifically hypofunction of the N-methyl-D-aspartate receptor (NMDAR). In addition, it has been proposed that NMDAR hypofunction may paradoxically cause an increase in glutamate release and hypermetabolism in corticolimbic regions. If a state of partial, chronic NMDAR blockade underlies schizophrenia, then schizophrenic volunteers (SV) may have greater glutamate release and associated elevations in regional cerebral blood flow (rCBF) than n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 54 publications
6
66
1
Order By: Relevance
“…[60,61] Likewise, rodent studies showed that ketamine treatment causes rapid increases of glutamate transmission in PFC. [62] It is high likely that ketamine's actions on synapses might reverse the morphological and functional alterations in the medial PFC neurons caused by stress exposure. In a recent study, using optogenetic stimulation of infralimbic PFC, Fuckikami et al [63] showed that rapid and long-lasting antidepressant and anxiolytic effects of systemic ketamine administration is associated with increased number and function of spine synapses of layer V pyramidal neurons of PFC.…”
Section: Discussionmentioning
confidence: 99%
“…[60,61] Likewise, rodent studies showed that ketamine treatment causes rapid increases of glutamate transmission in PFC. [62] It is high likely that ketamine's actions on synapses might reverse the morphological and functional alterations in the medial PFC neurons caused by stress exposure. In a recent study, using optogenetic stimulation of infralimbic PFC, Fuckikami et al [63] showed that rapid and long-lasting antidepressant and anxiolytic effects of systemic ketamine administration is associated with increased number and function of spine synapses of layer V pyramidal neurons of PFC.…”
Section: Discussionmentioning
confidence: 99%
“…This hyper-excitation has been related to an increase in thalamo-cortical glutamatergic excitation of downstream cortical regions such as the anterior cingulate and retrosplenial cortices (Tomitaka et al, 2000;Holcomb et al, 2005). PET scan studies have shown that schizophrenic subjects respond to ketamine with higher hypermetabolism than normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent findings were observed by McKie et al (2007) using BOLD fMRI. Holcomb et al (2005) showed that ketamine increased cerebral blood flow (CBF) in the anterior cingulate and frontal cortices in both healthy volunteers and patients with schizophrenia. Earlier studies also reported that low doses of ketamine affect selectively the areas that are thought to be dysfunctional in schizophrenia such as the limbic cortex and basal ganglia (Morris et al, 2005;Soyka et al, 2005;Tamminga et al, 2003).…”
Section: Introductionmentioning
confidence: 99%